Media, Censorship and Content Regulation in Brazil: Juridical Aspects and the Differences of Concepts (Law, State and Telecommunications Review, 2012)
The article analyses the legal aspects of censorship during the military government (1964-1985) and the current content regulation on broadcasting stations in Brazil, in order to present a more appropriate and accurate reading of the constitutional principles of legal prohibition of censorship and public control over the media.